2019
DOI: 10.2217/fca-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width and Coronary Artery Disease Severity in Diabetic Patients

Abstract: Aim: The purpose of the study is to evaluate the relationship between red blood cell distribution width (RDW) and coronary calcium score in diabetic patients. Methods: Hematological parameters of 100 diabetic (Type II) patients were assessed. Computed tomographic angiography was used to asses coronary artery calcium (CAC) score. Results: Mean age of the study cohort was 55 years (males: 60%). Mean RDW was 12.7%. Mean CAC score was 243. There was a significant correlation between RDW and each of: CAC scores (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…14 Another study reported a statistical correlation between RDW values and coronary artery calcium scoring (r=0.53; p<0.001). 17 All these results, including the present study, indicated that RDW is a marker for CAD. In addition, in the ROC curve analysis of the present study, the results showed that RDW had a sensitivity of 80.0% and a specificity of 84.2% for diagnosing CAD when the cutoff value of RDW was 13.65%.…”
Section: Discussionsupporting
confidence: 75%
“…14 Another study reported a statistical correlation between RDW values and coronary artery calcium scoring (r=0.53; p<0.001). 17 All these results, including the present study, indicated that RDW is a marker for CAD. In addition, in the ROC curve analysis of the present study, the results showed that RDW had a sensitivity of 80.0% and a specificity of 84.2% for diagnosing CAD when the cutoff value of RDW was 13.65%.…”
Section: Discussionsupporting
confidence: 75%
“…According to our knowledge, this is the first study to report an association between RDW, NLR and dp-ucMGP. However, RDW has been repeatedly associated with other surrogate calcification markers, such as IMT [ 17 , 19 , 46 , 47 , 48 ], coronary calcium scores [ 49 ] and PWV [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A risk model based upon complete blood count including hematocrit value, platelet count, white blood cell count, mean corpuscular volume, mean corpuscular hemoglobin concentration and RDW value was used by some studies to predict mortality risk among suspected cardiovascular disease patients. 22 The inflammation in patient with CAD can be predicted by increased RDW level. Which can be an indicator of poor prognosis in patients of CAD and can be used as principal pathophysiological observation.…”
Section: Discussionmentioning
confidence: 99%